2014
DOI: 10.1186/1743-8977-11-17
|View full text |Cite
|
Sign up to set email alerts
|

A review and perspective of existing research on the release of nanomaterials from solid nanocomposites

Abstract: Advances in adding nanomaterials to various matrices have occurred in tandem with the identification of potential hazards associated with exposure to pure forms of nanomaterials. We searched multiple research publication databases and found that, relative to data generated on potential nanomaterial hazards or exposures, very little attention has focused on understanding the potential and conditions for release of nanomaterials from nanocomposites. However, as a prerequisite to exposure studying release is nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 115 publications
(313 reference statements)
2
118
0
1
Order By: Relevance
“…The major analytical challenges in the case of migrations studies of FCMs are the typically low concentrations of migrating ENOs and the fact that mainly very small ENOs are expected to migrate. Similar challenges are reported for the detection and characterisation of ENOs in the environment (Nowack et al 2012;Froggett et al 2014). An overview of the techniques used for studying the migration of ENOs from FCMs, their corresponding LODs, and the information that can be obtained is given in Table 2.…”
Section: Open Question 2: If Migration Of Enos Occurs What Is the MIsupporting
confidence: 55%
See 1 more Smart Citation
“…The major analytical challenges in the case of migrations studies of FCMs are the typically low concentrations of migrating ENOs and the fact that mainly very small ENOs are expected to migrate. Similar challenges are reported for the detection and characterisation of ENOs in the environment (Nowack et al 2012;Froggett et al 2014). An overview of the techniques used for studying the migration of ENOs from FCMs, their corresponding LODs, and the information that can be obtained is given in Table 2.…”
Section: Open Question 2: If Migration Of Enos Occurs What Is the MIsupporting
confidence: 55%
“…The migration mechanisms will most likely depend on the properties of the ENO (e.g., size, shape, chemical composition), the properties of the given polymer (e.g., density, viscosity, solubility, (bio)degradability, swelling behaviour) and the distribution of the ENOs within the FCM (e.g., homogenous, surface-bound, only in the inner layer). Desorption, dissolution, and degradation processes and the influence of external factors such as UV radiation and abrasion are also considered in studies that focus on the environmental release of ENO, like titanium dioxide nanoparticles from painted surfaces or carbon nanotube from composites (Nowack et al 2012;Froggett et al 2014). More emphasis should be placed on the exchange of knowledge within food and environmental research on the potential mechanism and factors affecting the release of ENO from polymers.…”
Section: Open Question 2: If Migration Of Enos Occurs What Is the MImentioning
confidence: 99%
“…In addition, nanomaterials may be released in a form different from that in which they were added -particles can be changed through chemical reactions or through agglomeration or aggregation. & Weathering or machining of products may increase the potential for particle release, but there is some evidence (albeit incomplete and limited) that the nanomaterials released are often still bound to the underlying matrix rather than being free nanoscale particles (Froggett et al, 2014;West et al, 2016). & Nanoparticles can be released from products that did not intentionally contain nanomaterials -thus the demolition of traditional concrete produces particles of many sizes, including the nanoscale (Azarmi et al, 2014(Azarmi et al, , 2015.…”
Section: 'Nanoparticle Exposure Is Predictable'mentioning
confidence: 99%
“…Other studies have shown that when nano-enabled construction products are exposed to weathering and machining most of the particles released are attached to pieces of the matrix in which they are embedded, reducing their toxicity. Review of this literature by Froggett et al ( 2014) reported that less than one third of studies undertaken found particles which were dissociated from the matrix. In a more recent study (West et al, 2016), a machining task on a nanotitanium coated roof tile released debris that was mostly either attached to the matrix or consisted of dissociated particles which were larger than nanoscale.…”
Section: What Is Known About the Potential For Exposure To Nanomaterimentioning
confidence: 99%